2006
DOI: 10.1590/s1516-35982006000500007
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis morfogênicas e estruturais de azevém anual (Lolium multiflorum Lam.) manejado sob diferentes intensidades e métodos de pastejo

Abstract: RESUMO -Um experimento foi conduzido com o objetivo de avaliar a influência de intensidades e métodos de pastejo nas características morfogênicas (taxa de elongação de folhas, taxa de surgimento de folhas, tempo de vida da folha) e estruturais (número de folhas verdes, comprimento de folhas e densidade populacional de perfilhos) de azevém em dois ciclos de avaliação.Os tratamentos experimentais consistiram de duas intensidades e dois métodos de pastejo (contínuo e rotacionado), em um delineamento em blocos com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
1
7
4
6
Order By: Relevance
“…One of the indications of relatively low competition for light among plants was the similarity between treatments (P>0.05, Table 1) for the values of tiller population density (TPD), since it should be expected that shorter swards (15cm) had presented a greater amount of smaller tillers and vice-versa (MATTHEW et al, 1995). The values (5640 tillers m -2 , on average) were greater than those reported by CAUDURO et al (2006) and DUCHINI et al (2014), who also used annual ryegrass under rotational stocking. Since assessments were performed in 10cm diameter PVC rings placed directly on the seeding rows, the values obtained practically did not consider the empty spaces between the rows, which probably caused an overestimation of the values.…”
Section: Resultscontrasting
confidence: 64%
“…One of the indications of relatively low competition for light among plants was the similarity between treatments (P>0.05, Table 1) for the values of tiller population density (TPD), since it should be expected that shorter swards (15cm) had presented a greater amount of smaller tillers and vice-versa (MATTHEW et al, 1995). The values (5640 tillers m -2 , on average) were greater than those reported by CAUDURO et al (2006) and DUCHINI et al (2014), who also used annual ryegrass under rotational stocking. Since assessments were performed in 10cm diameter PVC rings placed directly on the seeding rows, the values obtained practically did not consider the empty spaces between the rows, which probably caused an overestimation of the values.…”
Section: Resultscontrasting
confidence: 64%
“…This value was also higher than that observed by Cauduro et al (2006), which was 276 degree-days/leaf of Italian ryegrass when managed under intermittent stocking.…”
Section: Resultscontrasting
confidence: 63%
“…Pontes et al (2003) observed higher values of elongation rate and leaf blade final size as the canopy height was increased. Cauduro et al (2006) also found higher rates of elongation of Italian ryegrass when it was managed under low grazing intensity. However, information regarding the effects of grazing intensity on growth of Italian ryegrass in mixture with black oats is still insufficient and needed, given the relevance of intercropping systems on livestock production in southern Brazil.…”
Section: Introductionmentioning
confidence: 81%
“…Isso porque a taxa de aparecimento foliar determina o potencial de gemas e de ocupação de sítios, que juntos determinam a taxa de aparecimento de perfilhos (DAVIES, 1974). O valor observado para densidade de perfilhos é 36,73% inferior ao relatado por PONTES et al (2003), de 4.614,4 perfilhos m -2 e 20,77% inferior aos 3.684,8 perfilhos m² encontrados por CAUDURO et al (2006). Essa diferença pode ser atribuída à adubação nitrogenada, 75kg ha -1 de nitrogênio, bastante inferior à utilizada por esses autores (150kg ha -1 ).…”
Section: Resultsunclassified